Proposal for a strategic management plan for experimental agricultural and academic farm “el cairo” of arauca (2014)
This paper presents a design for a strategic management plan for the Experimental Agricultural and Academic Farm: El Cairo of the Universidad Nacional de Colombia, Orinoquia branch. A non-experimental methodological design was used, from which a situational analysis of the farm was generated, which was used as a basis to formulate and design a Strategic Management plan for a five-year period. It was concluded that the current organization and management plan does not meet the mission objectives of research, teaching, and continuing education, suggesting a need for the articulation of the farm with the administrative and academic structure of the university in carrying out the strategic management plan derived from the current research.